Fibre enrichment of wheat flour with mesquite (Prosopis spp.): Effect on breadmaking performance and staling - Bigne, Facundo (2016)
Leguminous flours provide both nutritional and functional benefits when they are incorporated in a bread formula. Mesquite tree, (genus Prosopis) is widespread in semiarid regions of America and its fruit contains a high proportion of sugars, minerals and fibre. The objective of the present study was to analyse the effect of wheat replacement with different levels (15-35 g/100g) of mesquite flour (from Prosopis alba pods) on the leavening performance of dough, the nutritional and technological quality of bread and bread staling. Farinograph assays were applied to obtain optimum water amounts and development times. The addition of mesquite led to less stable dough with respect to control wheat dough. Fermentation assays showed higher fermentation times and lower maximum volumes. High levels of mesquite led to lower specific volumes of breads and a more compact and darker crumb, with smaller alveolus size, higher firmness and lesser resilience and cohesiveness. Breads were considerably improved in fibre content (6-9 g/100g). During storage, hardness and chewiness increased while cohesiveness and resilience decreased in all formulations. Nevertheless, textural changes were attenuated in composite breads in comparison with wheat bread. X-ray difractometry and differential scanning calorimetry (DSC) also indicated less retrogradation in these products.